Lymphocyte blastogenesis and interferon production in adult human leukocyte cultures stimulated with cytomegalovirus antigens. - Starr, S E (1980)
Lymphocyte blastogenesis and interferon production were measured in adult human leukocyte cultures stimulated with purified or crude cytomegalovirus antigens. Leukocytes from seropositive adults underwent blastogenesis when stimulated with purified or crude Towne strain antigen, whereas neither antigen stimulated blastogenesis in cultures from seronegative donors. The concentrations of antigens yielding maximal blastogenesis varied among the individuals tested. When cultures from seropositive individuals were stimulated with antigens prepared from three different CMV strains--AD-169, Towne, and Davis--comparable levels of blastogenesis were detected. Type 1 interferon was detected in supernatants of cultures stimulated with crude antigens regardless of the immune status of the donor. In contrast, when purified antigen was used as the stimulant, only cultures obtained from seropositive individuals produced detectable levels of interferon, which appeared to be predominantly type 2 or immune interferon.